Sentral Elektronik Di Pekanbaru Dengan Pendekatan Arsitektur High-Tech - Latif, A Haryadi; Susilawati, Mira Dharma; Aldy, Pedia (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
The development of the Electronic Industry in Pekanbaru is increasing every year. But in the development of the Electronic Industry, many electronic sellers are spreading and not centralized in the city of pekanbaru. An obstacle for the community to look for information on electronic goods, so that it can be concluded that the means of promotion and information are inadequate. An electronic is needed for seller facility or facility centered in Pekanbaru city to bring people together in searching for electronic goods, therefore to overcome these problems, a container such as Electronic Central is needed to provide facilities for electronic entrepreneurs in Pekanbaru. Electronic Central design uses the principles of High-tech Architecture and uses the concept of technological advancements that can provide the latest electronic technology developments to the people of Pekanbaru.Keyword : Electronics Central, High-Tech Architect